Engaging English Learners: Using AI to Integrate Local Legends into Language Lessons in West Kalimantan - Mulyani, Fitri; Elvina, Elvina; Yuliana, Yohanes Gatot Sutapa; Riyanti, Dwi (FKIP - Universitas Tanjungpura, 2025)
This study explored English teachers' views on incorporating local legends into lessons in West Kalimantan and how AI may help incorporate local legends and engage students using a survey approach. Data were collected from 24 teachers using purposive sampling. The survey revealed that while 70.8% of teachers expressed an interest in using local legends, only 4.2% regularly integrated them into their teaching, indicating a gap between enthusiasm and practice. Although half of the teachers believed that local legends could enhance student engagement, few considered them extremely effective, suggesting the need for more evidence of their impact. Barriers to the use of local legends include limited resources, lack of knowledge, time constraints, and varying student interests. This study highlights the potential of Artificial Intelligence (AI) in overcoming these challenges by providing resources, diversifying materials, and streamlining lesson planning. AI could bridge the gap between teachers' interest in local narratives and their actual use, promoting a more engaging, culturally relevant learning environment. However, the study's small sample size and short data collection period limited the generalizability of the findings. Future research should involve a larger, more diverse sample and longer data collection to provide more comprehensive insights.